Empirical investigation on determinants of national saving in Ethiopia - OLKAMO, Degefe Anulo (KDI School, 2021)
National saving is one of the driver sources for sustaining economic growth. However, low savings are cited as a constraint to sustained economic development in Ethiopia. The key aim of the study is to identify the determinant of national saving. The research carried out an Augmented Ducky-Fuller test to examine the stationary variables. The co-integration bound test scheme was applied to see the long-run association between variables. The result has shown that budget deficit, inflation rate, working-age dependency ratio, and trade openness, and deposit interest rate negatively determined national saving. Whereas; the GDP growth rate and broad money supply were positively affected in the long run. Based on these findings, the following policy implications suggest that prudent fiscal policy should be designed with a well-managed expenditure policy to reduce government budget deficits. The central bank needs hard work to enhance financial deepening and liberate deposit interest rates to ensure sustained savings. Give priority to establish a stable macroeconomic situation that will help to handle highly fluctuating prices. The age dependency ratio negatively affects the saving in the long run; therefore, the government should have worked to become out of the baby boom generations will positively contribute to the savings.
Thesis(Master) -- KDI School: Master of Public Policy, 2021
Keywords: Finance, Public--Ethiopia